2017
DOI: 10.1007/s10902-017-9895-5
|View full text |Cite
|
Sign up to set email alerts
|

Children’s and Adolescents’ Conceptions of Happiness at School and Its Relation with Their Own Happiness and Their Academic Performance

Abstract: Castilla, B. Children's and Adolescents' Conceptions of Happiness at School and its Relation with their own Happiness and their Academic Performance. Journal of Happiness Studies. This article may be used for non-commercial purposes in accordance with the Springer Terms and Conditions for Self-Archiving.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
28
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 54 publications
6
28
0
1
Order By: Relevance
“…Although this difference could be attributed to a children’s positive bias to see their life in an overly positive way (likely due to their cognitive limitations to properly compare between real and ideal situations; Harter, 2012), it may also indirectly reveal information about the drop in psychological wellbeing during the transition from childhood to adolescence. A consistent number of studies, indeed, clearly showed that children tend to experience higher wellbeing than adolescents in both general (Ronen et al, 2016) and domain specific evaluations (e.g., at school; López-Pérez and Fernández-Castilla, 2018). Some authors (e.g., Denscombe, 2000) have explained such differences considering the challenges that adolescents experience, especially in the school context (e.g., higher academic demands), which may threaten their sense of autonomy, competence, and relatedness, thereby ultimately influencing their POS and wellbeing.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Although this difference could be attributed to a children’s positive bias to see their life in an overly positive way (likely due to their cognitive limitations to properly compare between real and ideal situations; Harter, 2012), it may also indirectly reveal information about the drop in psychological wellbeing during the transition from childhood to adolescence. A consistent number of studies, indeed, clearly showed that children tend to experience higher wellbeing than adolescents in both general (Ronen et al, 2016) and domain specific evaluations (e.g., at school; López-Pérez and Fernández-Castilla, 2018). Some authors (e.g., Denscombe, 2000) have explained such differences considering the challenges that adolescents experience, especially in the school context (e.g., higher academic demands), which may threaten their sense of autonomy, competence, and relatedness, thereby ultimately influencing their POS and wellbeing.…”
Section: Discussionmentioning
confidence: 79%
“…Although a few studies considered the effect of POS during early adolescence (e.g., Tian et al, 2018), to the best of our knowledge, there is a lack of research on POS and the measurement properties of the P Scale among children. Since previous research indicated that (a) the onset of mental health issues may occur before adolescence (World Health Organization [WHO], 2013) and (b) children and adolescents tend to differ in their level of psychological wellbeing (i.e., children have higher psychological wellbeing than adolescents; see López-Pérez and Fernández-Castilla, 2018), looking at the role of POS during childhood and early adolescence may help us understand the dispositional bases of early psychological problems as well as may inform the design of intervention programs aimed at promoting mental and behavioral health from a young age (e.g., Social and Emotional Learning Programs; Collaborative for Academic Social and Emotional Learning [CASEL], 2013). From a developmental perspective, we focused on late childhood and early adolescence, as during this transitional phase, the self-system at the core of POS becomes more coherent and organized and children’s self-evaluations tend to be more accurate compared to the ones provided by younger children (for a more in depth discussion, see Harter, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Children valued more hedonic conceptualisations of wellbeing at school (positive feelings) whereas adolescents valued more eudaimonic forms (achievement). Interestingly, however, later work conducted by López-Pérez and Fernández-Castilla (2018) discovered that eudaimonic wellbeing played an important role in relation to Primary pupils’ objective achievement; pupils who conceptualised happiness as ‘learning’ had significantly higher achievement, but not happiness. Whereas, Secondary pupils conceptualising happiness as ‘being with friends’, ‘being praised’, ‘helping’ and ‘having no leisure time’ had higher achievement and happiness.…”
Section: Wellbeing and Achievement: Incompatible Or Underexplored?mentioning
confidence: 99%
“… 8. I note that López-Pérez and Fernández-Castilla (2018) use a single-item measure of pupils’ happiness in school, which somewhat limits findings, but this was not the only measure of wellbeing in their study (pupils’ conceptions of happiness are also used). …”
mentioning
confidence: 99%
“…Although the previous studies have advanced our understanding of the possible causes and consequences of happiness, they have investigated the role of happiness strictly relying on quantitative data. However, other research has stressed the importance of studying happiness from a qualitative point of view (e.g., Freire, Zenhas, Tavares, & Iglésias, 2013) to obtain a more in depth understanding of what children and adolescents comprehend what being happy at school is for them (López-Pérez & Fernández-Castilla, 2018). Investigating children's and adolescents' conceptualizations of happiness is important for different reasons.…”
Section: What Do Children and Adolescents Understand By Happiness?mentioning
confidence: 99%